THE RELEVANCE OF FINANCIAL LITERACY AND CULTURAL INHERITANCE IN HOUSEHOLD FINANCE DECISION-MAKING - Goso Goso (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The role of households in the financial system, which is a source of household financial complexity, has received insufficient attention. We will investigate how the importance of financial literacy and culture is related to husband and wife's knowledge, skills, and beliefs, as well as their agreement in making decisions about life insurance participation. Married couples conduct separate in-depth interviews, with wives conducting separate interviews and husbands conducting joint interviews. The main topic we cover is how to perform cognitive mapping on data derived from interviews with people of different ethnicities and cultures. The findings of this study confirm that cases in households with a strong individual cultural background where household financial decisions are delegated to the spouse are prevalent. The opposite is true for household couples with a collectivist cultural background, who intends to allow household financial decisions and reach consensus, avoiding the risk of uncertainty with life insurance consumer decision-making. This research project has implications for how financial knowledge is perceived, as well as how income and consumption are allocated. Individuals and couples gain confidence in household financial matters; sources of important decisions made prior to entering the financial markets; placement of investment assets in financial markets; and, finally, the positioning of households as the final owners of productive enterprises in the economy.